Komunikasi Adaptif Guru dengan Siswa Berkebutuhan Khusus Tunagrahita dalam Upaya Membangun Kemandirian di SLBN 8 Jakarta - Muhammad Fadhly; Novi Andayani Praptiningsih; Yulia Rahmawati (Yayasan Literasi Sains Indonesia, 2026)
Limitations in language processing and attention among students with intellectual disabilities often hinder full comprehension of classroom instructions, requiring teachers to adapt their communication to support learning and the development of functional independence. This study aims to describe teachers’ adaptive communication when interacting with students with intellectual disabilities at SLBN 8 Jakarta as an effort to build student independence. A qualitative approach with a descriptive case study design was employed. Data were collected through classroom observation, in-depth interviews, and documentation involving three teachers, three Grade 8 students as informants, and one senior special education teacher or expert; data were analyzed using the interactive model of Miles, Huberman, and Saldaña. Findings indicate that adaptive communication is dominated by convergence strategies in Communication Accommodation Theory, including concise and concrete verbal instructions, breaking tasks into small steps, repeating key words, and checking comprehension. Nonverbal support is provided through demonstrations, gestures, eye contact, friendly facial expressions, and the use of visual or multimedia aids. Relational elements appear through emotional support, a calming tone of voice, and positive reinforcement, while limited divergence emerges when teachers assert rules to regain students’ focus. Together, these strategies promote students’ functional independence, such as initiating tasks, following work sequences, seeking help appropriately, preparing learning tools, and tidying up after activities. The findings highlight the need for consistent strategies across teachers and strengthened school–home collaboration to sustain independent habits across situations.